Outcome of Ischemic Stroke Patients Following Decompressive Craniectomy: A Cohort Study - Mohammad Jamali; Mahyar Noorollahi; Ehsan Mohammad Hosseini; Abdolkarim Rahmanian; Mohammad Sayari; Sulmaz Ghahramani (Iranian Journal of Medical Sciences)
Background: Decompressive craniectomy (DC) is effective in reducing mortality and improving outcomes in stroke patients. However, there is a need for a better understanding of the outcomes and complications of stroke, particularly in regions such as Iran, where comprehensive studies on DC outcomes are scarce. This study investigated the effects of DC in stroke patients. Methods: This cohort study was conducted at Nemazi Hospital in Shiraz, Iran, from 2018 to 2020. All patients aged over 18 years with ischemic stroke requiring DC were included using census sampling. Data on demographics, clinical history, and imaging findings were collected. Outcomes were assessed using the modified rankin scale (mRS), Glasgow outcome score extended (GOSE), and aphasia severity rating (ASR). Results: A total of 144 cerebral infarction patients underwent DC; 22 (15.3%) were lost to follow-up, and 67 (55%) of the remaining patients died either during hospitalization or within at least 6 months of follow-up. Patients over 60 years old (OR=0.152), those with a history of stroke (OR=0.227), and those with COVID-19 infection (OR=0.164) were associated with a decreased likelihood of survival. However, an increase in the Glasgow Coma Scale (GCS) score on admission was associated with an increased probability of survival (OR=1.199). The ordered logistic regression analysis showed that an increase in GCS score was associated with a higher probability of achieving better outcomes across all models: GOSE (OR=1.177), mRS (OR=0.839, with lower scores indicating better outcomes), and ASR (OR=1.354). The analysis showed that patients over 60 had a lower probability of achieving better outcomes in the GOSE model (OR=0.185) and were likely to have worse outcomes in the mRS model (OR=5.182).Conclusion: These findings underscored the critical role of comorbidities (such as COVID-19 and prior stroke) and GCS scores in predicting patient survival and functional outcomes following DC. In particular, the higher mortality rates and poorer functional outcomes observed in older patients highlighted the need for careful consideration in this age group.